P361 Patterns of use and durability of initial and sequential biological agents in a large Paediatric inflammatory bowel disease observational cohort. (16th January 2018) - Kaplan, J; Liu, C; King, E; Bass, J; Patel, A; Tomer, G; Tung, J; Pratt, J; Chen, S; Lissoos, T; Colletti, R; ,
Abstract: Background: Biological agents (BA) are indicated for treatment of children with moderately to severely active ulcerative colitis (UC) and Crohn's disease (CD). However, many children do not respond or lose response and require sequential BA treatment. The aims of this study were to determine the frequency and patterns of initial and sequential BA use and BA durability in a large paediatric inflammatory bowel disease (IBD) cohort. Methods: We performed a retrospective study using data from ImproveCareNow (ICN), a multicentre paediatric IBD registry. BA use and other clinical data were obtained directly from the ICN database. A subset of registry patients who were treated with their first BA after enrolment into ICN (chart review cohort), had additional clinical information obtained by chart review at 39 participating ICN sites. Results: Of the 17649 IBD patients (12410 CD, 5239 UC) diagnosed before 18 years of age, 7585 (43%) were treated with a BA before age 18, including 50.5% of CD patients. CD patients were more likely to be treated with a BA than UC patients (odds ratio, 3.0; 95% confidence interval, 2.8–3.2; p ≤ 0.0001). In the chart review cohort ( n = 1029: 809 CD, 220 UC), the first BA was an anti-TNF agent in all cases (88% infliximab, 12% adalimumab). The median time from diagnosis to BA initiation was shorter in CD than in UC (325 vs. 423 days; p = 0.004). The probability of remaining on the first BA was higher in CD than UC [0.93 vs. 0.84 at 6 month old; 0.85 vs. 0.75 at 12 month old; 0.79 vs. 0.66 at 24 month old; 0.74 vs. 0.55 at 36 month old; p = <0.0001, Figure 1]. The most common reasons for discontinuation of the first BA in all patients were secondary loss of response (39%), intolerance (23%), and primary non-response (PNR) (19%). PNR was a more common reason for discontinuation in UC than in CD (29% vs. 15%, p = 0.02). Over a median follow-up of 1.56 years [interquartile range, 0.89–2.57 years], 17%, 2.3%, and 0.6% of patients were treated with at least two, three, or four BAs, respectively. The second BA was most commonly an anti-TNF agent (94.8%). Vedolizumab was the second BA in 4.6% of cases and the third in 37.5% of cases. In CD, the probability of remaining on the second BA was 0.85, 0.76, 0.72, and 0.64 at 6 months, 12 months, 24 months, and 36 months, respectively. Conclusions: In this large cohort, BAs were used in >25% of children with UC and >50% of children with CD before 18 years of age. BA discontinuation and sequential BA treatment was relatively common. BAs were used earlier and the first BA was more durable in CD than in UC.